Financial Sustainability of Local Governments in Indonesia - Iqbal Lhutfi; Harpa Sugiharti (Universitas Pendidikan Indonesia, 2022)
This study aims to examine the factors that impact the financial sustainability of local governments in Indonesia. This study used a quantitative method and employed the secondary data processing of the Regional Government Financial Reports (LKPD) for 2018–2020 retrieved from The Audit Board of the Republic of Indonesia (BPK). This study used a saturated sample that included every member of the population, precisely 34 Indonesian provinces. The author used multiple regression analysis of panel data by using Eviews 10. This study employed financial sustainability as the dependent variable, whereas total population, gross regional domestic product (GRDP), and financial independence acted as independent variables. This study concludes that total population and gross regional domestic product have a substantial negative impact on financial sustainability, while financial independence positively affects financial sustainability. This study adds new information about the financial sustainability of Indonesian provincial governments, providing theoretical support that future research can later expand upon. By taking into account variables that may impede or promote financial sustainability in each location, local governments can utilise this research to inform the policies they adopt to manage the finances of their respective regions.